Ligation of Left Renal Vein for Spontaneous Splenorenal Shunt to Prevent Portal Hypoperfusion after Orthotopic Liver Transplantation - Lampros Kousoulas; Kristina Imeen Ringe; Michael Winkler; Frank Lehner; Nicolas Richter; Juergen Klempnauer; Fabian Helfritz (Case Reports in Transplantation)
We report a case of recovered portal flow by ligation of the left renal vein on the first postoperative day after orthotopic liver transplantation of a 54-year-old female with alcoholic liver cirrhosis, chronic kidney failure, and spontaneous splenorenal shunt. After reperfusion, Doppler ultrasonography showed almost total diversion of the portal flow into the existing splenorenal shunt, but because of severe coagulopathy and diffuse bleeding, ligation of the shunt was not attempted. A programmed relaparotomy was performed on the first postoperative day, and the left renal vein was ligated just to the left of the inferior vena cava. Portal flows subsequently increased to 37 cm/sec, and the patient presented a good and stable liver function. We conclude that patients with known preoperative splenorenal shunts should be closely monitored, and if the portal flow becomes insufficient, ligation of the left renal vein should be attempted in order to optimize the portal perfusion of the liver.